A Numerical Study on the Impact of Cathode Catalyst Layer Loading on the Open Circuit Voltage in a Proton Exchange Membrane Fuel Cell. Issue 4 (19th April 2021) - Moore, Michael; Shukla, Shantanu; Voss, Stephan; Karan, Kunal; Weber, Adam; Zenyuk, Iryna; Secanell, Marc
Abstract : The open circuit voltage (OCV) in a proton exchange membrane fuel cell (PEMFC) is typically recorded as being approximately 300 mV lower than the equilibrium voltage computed by the Nernst equation. While a number of causes have been proposed, the voltage drop is generally attributed to the oxidation of crossover hydrogen in the cathode. A single phase, through-the-channel model is presented that includes hydrogen transport across the membrane, an empirical model for the hydrogen oxidation reaction (HOR) fit to experimental data obtained at high potentials and a multi-step kinetic model to describe the oxygen reduction reaction (ORR). Model predictions were compared to experimentally obtained OCVs and the results show that the model is capable of capturing the experimentally observed changes in OCV with platinum loading, as well as fuel cell performance; and that, at low Pt loadings, small quantities of unreacted hydrogen leave the cathode because the HOR is kinetically limited by oxide blocking and anion adsorption. A parametric study is used to show that a minimum OCV is achieved at ultra-low loadings. Results also show that only a multi-step ORR model can simultaneously capture polarization data and the OCV.